Shock deformation microstructures in xenotime from the Spider impact structure, Western Australia - Cox, Morgan A.; Cavosie, Aaron; Poelchau, M.; Kenkmann, T.; Bland, Phil; Miljkovic, Katarina (2021)
The rare earth element-bearing phosphate xenotime (YPO4) is isostructural with zircon, and therefore it has been predicted that xenotime forms similar shock deformation microstructures. However, systematic characterization of the range of microstructures that form in xenotime has not been conducted previously. Here, we report a study of 25 xenotime grains from 10 shatter cones in silicified sandstone from the Spider impact structure in Western Australia. We used electron backscatter diffraction (EBSD) in order to characterize deformation and microstructures within xenotime. The studied grains preserve multiple sets of planar fractures, lamellar {112} deformation twins, high-angle planar deformation bands (PDBs), partially recrystallized domains, and pre-impact polycrystalline grains. Pressure estimates from microstructures in coexisting minerals (quartz and zircon) allow some broad empirical constraints on formation conditions of ∼10-20 GPa to be placed on the observed microstructures in xenotime; at present, more precise formation conditions are unavailable due to the absence of experimental constraints. Results from this study indicate that the most promising microstructures in xenotime for recording shock deformation are lamellar {112} twins, polycrystalline grains, and high-angle PDBs. The {112} deformation twins in xenotime are likely to be a diagnostic shock indicator, but they may require a different stress regime than that of {112} twinning in zircon. Likewise, polycrystalline grains are suggestive of impact-induced thermal recrystallization; however, in contrast to zircon, the impact-generated polycrystalline xenotime grains here appear to have formed in the solid state, and, in some cases, they may be difficult to distinguish from diagenetic xenotime with broadly similar textures.